PENGARUH STRUKTUR MODAL, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP KUALITAS LABA - Sri Ernawati, 14.05.52.0034; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2018)
Thepurpose of this studyis toexaminesand analysesthe effect of firm capital structure, liquidity, and company size to earning quality. This research was conducted atbase manufacture listed on Indonesia Stock Exchange (BEI).The sampling method used in this study ispurposive sampling with observation period 2014 to 2016 the number of samples obtained as much as 58. Theinfluence between variablesis discribed by using multiple regression analysiswith SPSS 23 program. The type of data used is secondary data.The results showed that the capital structure has a significant negative effect on earning quality, liquidity and company size do not significantly affect the earning quality. Keywords:Firm capital structure, liquidity, company size, and earning quality